1989
DOI: 10.1542/peds.83.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Breast Milk Production for Premature Infants With a Relaxation/Imagery Audiotape

Abstract: Many women whose premature infants are hospitalized in a newborn intensive care unit choose to express breast milk for their babies. Yet anxiety, fatigue, and emotional stress are powerful inhibitors of lactation. To facilitate the breast-feeding experience, intervention mothers were given a 20-minute audio cassette tape based on relaxation and visual imagery techniques. At a single follow-up expression of milk at the hospital approximately 1 week after enrollment, they expressed 63% more breast milk than a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(38 citation statements)
references
References 0 publications
1
34
0
2
Order By: Relevance
“…An RCT by Feher et al demonstrated that mothers pumping for infants in the NICU produced more milk when asked to listen to a relaxation exercise recording on a daily basis prior to pumping. 32 Higher frequency of use of the intervention correlated with increased milk volume. Although women in the Feher et al trial shared diverse economic characteristics and gave birth at a similar gestational age to women in our study, it appears that the women in the control arm lacked support from a lactation consultant.…”
Section: Discussionmentioning
confidence: 97%
“…An RCT by Feher et al demonstrated that mothers pumping for infants in the NICU produced more milk when asked to listen to a relaxation exercise recording on a daily basis prior to pumping. 32 Higher frequency of use of the intervention correlated with increased milk volume. Although women in the Feher et al trial shared diverse economic characteristics and gave birth at a similar gestational age to women in our study, it appears that the women in the control arm lacked support from a lactation consultant.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, relaxation group infants were also reported to sleep longer, have higher milk intake, and demonstrate greater weight gain (Mohd Shukri et al 2019). Other experimental studies using relaxation therapies, such as meditation and music therapy, showed beneficial effects of the intervention on milk volume or expression, energy and milk fat (Ak et al 2015;Dabas et al 2019;Feher et al, 1989;Keith, Weaver, and Vogel 2012;Kittithanesuan et al 2017;Varişoğlu and Güngör Satilmiş 2020). Furthermore, milk energy density, fat, and medium-chain and long-chain saturated fatty acids were also found to be associated with long-term stress during the postpartum period (Ziomkiewicz et al 2021b).…”
Section: Maternal Mental Healthmentioning
confidence: 97%
“…Two draft audio files were sent to contributors, both had been used in previous RCTs [41][42][43]. Contributors were asked for detailed feedback, both open ended and specific and to choose their preferred recording.…”
Section: Stage 5 -Rct Intervention Modification Exercise Structurementioning
confidence: 99%